Evaluación del comportamiento de la protección de distancia (21) considerando el efecto Infeed en diferentes escenarios de operación. - Padilla Choca, Paola Jaqueline (2023)
In the present research project, the behavior of the distance protection (21) in the Santo Domingo – Baba and Baba – Quevedo transmission lines was analyzed, before the entry of the generators connected to the Baba bus, through the use of the DigSilent software Power Factory. The project included distance relays at the ends of the Santo Domingo – Baba and Baba – Quevedo transmission lines; the calibration of the protections was carried out without considering the generators connected to the Baba bar. Thus, when a generator enters the system, the protection presents problems to act in zone 2, because where previously it could recognize faults up to 50% away from the transmission line, now the relay operates up to 45% and 33% in triphasic and single-phase faults respectively. Finally, when two generators are connected to the SEP, the impact that the relay has on its scope of protection is greater, because in the backup zone the protection covers up to 41% and 25% of the L/T in three-phase and single-phase faults. respectively. Due to the contribution of currently generated by the infeed effect, the relays sensitivity decreases under fault conditions. Consequently, this causes an underreach as the relay measures fault impedances at a greater distance from the actual location of the fault point.